Handbook of big data - Bühlmann, Peter; Drineas, Petros; Kane, Michael (Michael John); Laan, M. J. van der (Boca Raton, FL CRC Press, an imprint of the Taylor & Francis Group, 2016)
"Handbook of Big Data provides a state-of-the-art overview of the analysis of large-scale datasets. Featuring contributions from well-known experts in statistics and computer science, this handbook presents a carefully curated collection of techniques from both industry and academia. Thus, the text instills a working understanding of key statistical and computing ideas that can be readily applied in research and practice"
The advent of data science: some considerations on the unreasonable effectiveness of data / Richard J.C.M. Starmans -- Big-n versus big-p in big data / Norman Matloff -- Divide and recombine: approach for detailed analysis and visualization of large complex data / Ryan Hafen -- Integrate big data for better operation, control, and protection of power systems / Guang Lin -- Interactive visual analysis of big data / Carlos Scheidegger -- A visualization tool for mining large correlation tables: the association navigator / Andreas Buja, Abba M. Krieger, and Edward I. George -- High-dimensional computational geometry / Alexandr Andoni -- IRLBA: fast partial singular value decomposition method / James Baglama -- Structural properties underlying high-quality randomized numerical linear algebra algorithms / Michael W. Mahoney and Petros Drineas -- Something for (almost) nothing: new advances in sublinear-time algorithms / Ronitt Rubinfeld and Eric Blais -- Networks / Elizabeth L. Ogburn and Alexander Volfovsky -- Mining large graphs / David F. Gleich and Michael W. Mahoney -- Estimator and model selection using cross-validation / Iván Díaz -- Stochastic gradient methods for principled estimation with large datasets / Panos Toulis and Edoardo M. Airoldi -- Learning structured distributions / Ilias Diakonikolas -- Penalized estimation in complex methods / Jacob Bien and Daniela Witten -- High-dimensional regression and inference / Lukas Meier -- Divide and recombine: subsemble, exploiting the power of cross-validation / Stephanie Sapp and Erin LeDell -- Scalable super learning / Erin LeDell -- Tutorial for causal inference / Laura Balzer, Maya Petersen, and Mark van der Laan -- A review of some recent advances in causal inference / Marloes H. Maathuis and Preetam Nandy -- Targeted learning for variable importance / Sherri Rose -- Online estimation of the average treatment effect / Sam Lendle -- Mining with inference: data-adaptive target parameters / Alan Hubbard and Mark van der Laan.
"Chapman & Hall book."
Includes bibliographical references and index.
Keywords: Big data -- Statistical methods -- Handbooks, manuals, etc